Sense-making with a little help from my friends - Tom Froese (Avant: Journal of Philosophical-Interdisciplinary Vanguard, 2012)
The work of Ezequiel Di Paolo and Hanne De Jaegher has helped to transform the enactive approach from relative obscurity into a hotly debated contender for the future science of social cognition and cognitive science more generally. In this short introduction I situate their contributions in what I see as important aspects of the bigger picture that is motivating and inspiring them as well as the rest of this young community. In particular, I sketch some of the social issues that go beyond mere academic debate, including how the methods and assumptions that inform orthodox cognitive science are intrinsically related to the critical state of affairs in our world today. I conclude with some personal recollections in order to give an idea of the context in which their ideas, and mine as well, came to fruition.